2018
DOI: 10.11648/j.ajhr.20180601.15
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Exclusive Breastfeeding Among Mothers Seen at the University of PortHarcourt Teaching Hospital

Abstract: Exclusive breastfeeding for the first six months of life is a natural, cost effective and feasible intervention that promotes child survival. Exclusive breastfeeding has been promoted severally but its practice has remained poor in Nigeria. This study aims to determine the knowledge and practice of exclusive breastfeeding among mothers who bring their children to the department of Paediatrics University of Port Harcourt Teaching Hospital. This was a descriptive cross-sectional hospital based study carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…This finding correlates with the 39.4% and 45% reported by Nukpezah et al [29] in Ghana and Sultania et al [25] in India. This result is however lower than the 53%-64.6% reported in other studies conducted in Nigeria [3,11] and Ethiopia [21]. It was however higher than the 31% reported by Al Banali in Saudi Arabia [23].…”
Section: Discussioncontrasting
confidence: 63%
See 4 more Smart Citations
“…This finding correlates with the 39.4% and 45% reported by Nukpezah et al [29] in Ghana and Sultania et al [25] in India. This result is however lower than the 53%-64.6% reported in other studies conducted in Nigeria [3,11] and Ethiopia [21]. It was however higher than the 31% reported by Al Banali in Saudi Arabia [23].…”
Section: Discussioncontrasting
confidence: 63%
“…The prevalence rate of exclusive breastfeeding for 6 months observed in this study compares to the observed 43.6% reported by Wolde et al [21] in a study carried out in Ethiopia. There is a better EBF practice in this study compared to the earlier studies in Port Harcourt carried out about 3-4years before this study, that reported EBF prevalence of 11.7% [11] and 22.5% [12]. This probably highlights the fact that dissemination of EBF information by health workers and media outlets is yielding results, although there is still room to do more.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations